Indonesian folktales: feminism and the query of femaleness - Sulasih Nurhayati (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2019)
This paper aims  to study about the query of femaleness in Indonesian  folktales from  the feminism approach. It  is taken into account due to  women’s subordination that allegedly implies the negation of femaleness. In  particular,  the perpetual story of  Malin Kundang  represents that  owing to  her weakness, a woman is  a subordinate creature.  It happens when Malin  Kundang denies the appearance of her mother after a series of successes he  makes.  Another popular story,  Sangkuriang, even depicts that due to her  beauty, a woman is an  object of sex.  It is  seen when Sangkuriang  proposes Dayang Sumbi  to be his wife because of his inability of recognising her as  his mother after some year banishment. The subordination eventually drives  the two  women to struggle against it  in order to  defend their dignity.  The  mother of Malin Kundang spells him to be a stone and Dayang Sumbi  overtly refuses Sangkuriang’s proposal.  Their  struggles  are of course  valued of the morality for wider public, too.  Despite this, the tales remain a  query of women’s existence, particularly that of femaleness. The truth that a  woman is  biologically and socially  the mother of man is denied in order to  sustain men’s superiority.  By biologically it means that a woman is the  undenied creature for her gifted power of  childbirthing. It  then socially gives her  more power to sustain the generations and the social  relationships.  Furthermore,  it is pivotal to  investigate  the feminist critical  ideas about the essence of femaleness in the Indonesian folktales.